Upaya guru pendidikan agama Islam dalam penanganan kasus verbal harassment untuk menjaga kesehatan mental siswa - Mufida, Arizzatul Aulia; Hidayat, Moch. Charis; Puspitasari, Ika (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2025)
Islamic Religious Education (PAI) teachers hold a strategic role in maintaining students’ mental health by preventing verbal harassment in schools. This study aims to analyze the strategies employed by PAI teachers in addressing verbal harassment at SMP Maryam Surabaya. Using a descriptive qualitative approach, data were collected through in-depth observation and interviews. The findings reveal that PAI teachers implement dialogic and narrative approaches to help students understand the negative impacts of verbal harassment. These approaches are reinforced by academic evaluations that include moral assessments as a preventive measure. In addition, religious values are integrated into the learning process to foster students’ social awareness. Despite various efforts, challenges such as student resistance remain. The study concludes that PAI teachers play a crucial role in creating a safe, inclusive school environment that supports students' mental well-being.